Faktor-faktor yang Berhubungan dengan Pendokumentasian Asuhan Keperawatan di Rumah Sakit Jiwa : Factors Associated with the Documentation of Nursing Care in Mental Hospitals - Putri Wulandini. S.; Tri Krianto; Yuyun Priwahyuni (Fakultas Keperawatan Universitas Andalas, 2016)
Behaviour is all the human’s action and activity, it can directly or undirectly be watched by other people. The documentation is the report and note prove that nurses hae done assessment, diagnoses, intervention, implementation and evaluation. The factors that relate with documentation behaviour are knowlegde, attitude, work load, suggestion, intensive and leadership. The kind of the reseach is analitics section study with overall of the samples are 93 nurses. The data analysis is done univariately, bivariately and multivariately with the multiple logictic regression. The reserch result is obtained that the unrelated Variable with the nursing nurture documentation behaviour is the leadership. Where as related variable with documentating behaviour is he knowledge OR 2-696 (95% CII.161-6.256), attitude OR 2.969 (95% CI 1.2746.920), insentive OR 0.293 (95% CI 0.121-0.708) and work load OR 3.569 (95% CI 1.510-8.433). Tthe most related variable is attitude. It is suggesed for the nursing management operates the education on colloquium or training rutinely. For increasing t he nurse’s atitude in nursing nurture documentation.